Leaving before bad times: Does the labor market penalize preemptive director resignations? - Dou, Ying (Journal of Accounting and Economics, 2017)
When firms experience negative events such as lawsuits or earnings restatements, their directors also suffer. But what about those who leave shortly before the events? I show that directors who leave prior to negative events experience greater declines in the number of their directorships than directors who stay through the events, but smaller declines than directors who leave after the events. These declines do not appear to be voluntary or driven by forced departures. Instead, they appear to be the results of labor market penalties. The results suggest that resigning pre-emptively does not protect directors from labor market penalties.